PENGEMBANGAN APLIKASI PENJADWALAN JANJI TEMU PASIEN BERBASIS ANDROID PADA KLINIK GIGI BMM DENTAL CARE - Muhamad Rafli Firdaus; Imay Kurniawan; Minarto (STKIP Subang, 2026)
BMM Dental Care still relies on manual appointment recording and unstructured communication through social media to run its daily operations. This semi-manual way of working often triggers patient queue buildup due to unpredictable arrival times, loss of communication history between patients and dentists as it gets scattered across various private conversations, and the risk of delayed responses to patient complaints. This study aims to design and build an Android-based appointment scheduling application involving two user roles, namely patients and dentists, as a digital solution for clinic administration. The application was developed using the Model-View-ViewModel (MVVM) architecture with Jetpack Compose for the interface, along with a local SQLite database wrapped by the Room Persistence Library so that the system remains fully operational offline-first. The results show that patients can independently register and create their own appointment schedules, communicate two-way with dentists through a real time chat feature, and receive notifications targeted according to their role and currently active account. Dentists, on the other hand, can monitor a daily schedule summary, search patient data, mark appointment status, and send promotions to all registered patients. System testing using the Black Box Testing method on all core functional scenarios — ranging from two-role registration and login to targeted notification delivery — showed a one hundred percent validity rate, indicating that the application is ready to support the daily operations of BMM Dental Care.